1991
DOI: 10.1007/bf03029727
|View full text |Cite
|
Sign up to set email alerts
|

Newer beta blockers and the treatment of hypertension

Abstract: Beta-adrenoceptor blocking agents are established as one of the principal classes of antihypertensive agents. Despite progressive refinements over the years, they still possess some unwanted effects, which limit their considerable value. In recent years a wide range of variations upon the beta-blocker theme has been developed. The full clinical advantages of the newer agents remain to be defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 115 publications
0
3
0
Order By: Relevance
“…Previous reports [1,2] showed that betaxolol, in contrast with other beta-blockers, has no adverse effect on lipid metabolism and carbohydrate metabolism. McAreavy et al [3] reviewed the new beta-blockers and the treatment of hypertension, and they reported that betaxolol decreases LDL cholesterol levels. McAreavy et al [3] reviewed the new beta-blockers and the treatment of hypertension, and they reported that betaxolol decreases LDL cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports [1,2] showed that betaxolol, in contrast with other beta-blockers, has no adverse effect on lipid metabolism and carbohydrate metabolism. McAreavy et al [3] reviewed the new beta-blockers and the treatment of hypertension, and they reported that betaxolol decreases LDL cholesterol levels. McAreavy et al [3] reviewed the new beta-blockers and the treatment of hypertension, and they reported that betaxolol decreases LDL cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…A more rational approach would be to lower blood pressure by correcting the damaged hemodynamic mechanism, i.e., by vasodilation [Zanchetti, 1987]. A new generation of β-blockers with a variety of additional characteristics is now emerging; the most interesting of these are β-blockers with vasodilating activity [Hampton, 1994;McAreavey et al, 1991;Prichard, 1991], achieved by a variety of mechanisms including α-receptor blockade, β 2 -agonism, and a dilator action independent of the α-and β-receptors. Such β-blockers reduce total peripheral resistance and bring about less suppression of cardiac output in exercise [Lund-Johansen, 1992].…”
Section: Introductionmentioning
confidence: 98%
“…adrenoceptors, intrinsic sympathomi metic activity (ISA), membrane-stabilizing ac tivity, and lipid versus water solubility [4,5], A new generation of p blockers with a vari ety of additional characteristics are now emerging. The most interesting of these are (3 blockers with vasodilating activity, achieved by a variety of mechanisms including a-adrenoceptor blockade, P-adrenoceptor agonism, and a dilator action independent of the a and p receptors [6][7][8], Such p blockers reduce total peripheral resistance and bring about less sup pression of cardiac output in exercise [9], For example, celiprolol is a p blocker character ized by selective blockade of Pi receptors and partial agonist activity on P2 receptor [ 10], Carvcdilol and labetalol are P-adrenoceptor antagonists which cause peripheral vasodila tion primarily via aj adrenergic blockade [ 10,11 ]. Regarding ISA, a nonselective p-adrenoceptor blocker such as vanidilol with partial p2-agonist activity has never been described.…”
Section: Introductionmentioning
confidence: 99%